Pengaruh Inflasi Dan Nilai Tukar Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2016 - Risma Kartikaputri (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to describe (1) Influence Inflation on Return On Equity on property and real estate companies listed on the BEI 2013-2016. (2) The Effect of Exchange Rates on Return On Equity on the property and real estate companies listed on the BEI 2013-2016. (3) Inflation Influence on Stock Return on BEI 2013-2016 (4) Effect of Exchange Rates on Stock Return on property and real estate companies listed on BEI 2013-2016. (5) Influence of Return On Equity to Stock Return on property and real estate companies listed on BEI 2013-2016 (6) Inflation Influence on Stock Return through Return on Equity in property and real estate companies listed on BEI 2013-2016. (7) ROE is unable to mediate the effect of exchange rate on stock returns. The sample of this research is 10 companies selected by using purposive sampling method. Data analysis used is multiple linear regression for. Variables that are independent of Return On Equity. The results showed (1) Inflation did not affect the Return On Equity (2) Exchange Rate does not affect Return On Equity (3) Significantly negative Inflation on Stock Return. (4) Significantly negative exchange rate of Return on Stock (5) Return On Equity does not affect to. (6) ROE able to mediate Inflation's effect on Stock Return. (7) ROE is unable to mediate influence. Keywords: Inflation, Exchange Rate, Stock Return, Return On Equity